Optimization Model in Logisticts Planning and Supply Chain. (August 2019) - Silaen, Nova Eliza; Sawaluddin,; Tulus,
Abstract: The progress and success of the company can be seen from the consumer's response to production from all aspects of each company's activities and is a key success factor. In this case describes the problem of supply chain optimization from the perspective of providing logistics including a mathematical model of cost optimization for supply chains in the form of MILP (Mixed Integer Linear). Production, transportation and distribution costs are chosen as optimization criteria. Time, volume, capacity and mode of transportation are also taken into account. The model was developed based on supply chain management theory to achieve the lowest cost, responsive and to achieve common goals. The results state that product inventories, loading patterns, modes of transportation, and minimum order quantities significantly affect the total logistics costs. Shorter production processing time, and produce optimal solutions. However, the right limits must be carefully defined to get a viable solution.